PIK3CA-Related Overgrowth Spectrum From Diagnosis to Targeted Therapy: A Case of CLOVES Syndrome Treated With Alpelisib - Pagliazzi, Angelica; Oranges, Teresa; Traficante, Giovanna; Trapani, Chiara; Facchini, Flavio; Martin, Alessandra; Semeraro, Alessandro; Perrone, Anna; Filippeschi, Cesare; Giglio, Sabrina (Frontiers in Pediatrics, 2021)
PIK3CA-related overgrowth spectrum (PROS) is an umbrella term referring to various clinical entities, which share the same pathogenetic mechanism. These conditions are caused by somatic gain-of-function mutations in PIK3CA, which encodes the 110-kD catalytic α subunit of PI3K (p110α). The common clinical denominator of PROS disorders is that they are sporadic conditions, presenting with congenital or early childhood onset overgrowth with a typical mosaic distribution. Traditional therapeutic approaches, such as sclerotherapy and surgical debulking, are often not curative in PROS patients, leading to a recrudescence of the overgrowth in the treated area. Specific attention has been recently paid to molecules that are used and studied in the oncogenic setting and that are targeted on specific alterations of the pathway PI3K/AKT/mTOR. We present an 8-year-old girl with CLOVES syndrome, born with a large cystic lymphangioma involving the left hemithorax and flank, multiple lipomas, and hypertrophy of the left foot and leg. She developed severe scoliosis. A Whole Exome Sequencing analysis performed on DNA extracted from a skin sample showed a mosaic gain-of-function variant in the PIK3CA gene (p.H1047R, 11% of variant allele frequency). Many therapeutic approaches, including treatment with Sirolimus, have been attempted, without benefit.Once molecular confirmation of our clinical suspicion was obtained, after a multidisciplinary evaluation, we decided to discontinue Sirolimus and start targeted therapy with Alpelisib (50 mg/day). We noticed a decrease in fibroadipose overgrowth at the dorsal level, an improvement in in posture and excellent tolerability.